(untitled) (Research, Society and Development, 2021)
In the teaching of mathematics, the need to bring proportionality closer to the student’s daily life has been increasingly discussed and the Inverted Classroom provides significant learning that can assist in this process. Therefore, the objective of this work is to present arguments that justify the use of the Inverted Classroom in the teaching of proportionality, as it is a methodology accessible to students and that follows the pace of current technologies. This research is a qualitative literature review study for the purpose of theoretical deepening on the subject. The results show that the Inverted Classroom intensifies the relationship between student and teacher, changes classroom management, allows conditions for students to pause and rewind the teacher and helps students to overcome differences. In this way, this research defends the approach of proportionality in a non-mechanized way, and that is closer to the reality of the students, making use of the Inverted Classroom as an instrument to enhance learning.